İlköğretim altıncı sınıf Tütkçe ders kitaplarındaki kelimeler ve bu kelimelerin kullanılabilirliği - Arı, Gökhan (My University, 2003)
Ders kitaplarında ve örnekletil gruplarının yazılı anlatımlarında en çok geçen kelime türü isimdir. 3. Ders kitaplarında ve örneklem gruplarının yazılı anlatımlarında Türkçe kelimeler, ödünçleme kelimelere göre daha fazla kullanılmıştır. Ödünçleme kelimeler içerisinde Arapça, Farsça ve Fransızca kökenli kelimeler daha fazla kullanılmıştır. 4. Ders kitaplarında ve örneklem gruplarının yazılı anlatımlarında en çok kullanılan kelime birdir. 5. Ders kitaplarında kullanım sayısı fazla olan kelimeler, örneklem gruplarının yazılı anlatımlarında da fazla kullanılmış, ders kitaplarında kullanım sayısı az olan kelimeler, örneklem gruplarının yazılı anlatımlarında ya kullanılmamış ya da az kullanılmıştır.

In this study, which is titled as the vocabulary involved in 3 Turkish textboks that are used in the 6lh grade of the Primary schools and the words which are taken part in the written expressions of the students who are reading these three textbooks as learning tools are examined. The books that are examined in this study are the following ones; Primary Education-Turkish textbook of the 6th Grade of the MEB press, of the Dörtel Press and of the Altın Kitaplar Press. The sample of the study included 184 students and while examining the sample, the written expressions of the students were considered. The subject matter of these writings was asked with this question: Please, write one of your memories that you could not forget. In this study, the following aspects are determined and compared; the words taken place in the 3 Turkish textbooks of the 6lh grade in the Primary Education; the number of these words; the number of the usage of these words and the propartion of the usage of them; the types of words and the origins of the used words. The words; the number of the words; the number of the usage of the words and the percentage of the usage of them; the types of words and the origins of the words, which were taken place in the written expressions of the sample groups who used these textbooks as tools were determined by means of using the scanning method, and then, these were transferred to the computer. The data of the study were evaluated in the computer environment. In this manner, the frequency of the words was arranged from the maximum usage to the minimum and the frequency percentages were taken. Tables were designed and interpreted according to the findings of the study. By taking, the results into consideration, the proposals were determined and peresented. The findings that are set according to the results of the study can be summarized as: 1. It's found that there are differences between the number of the words and of the usage of the words taken place in the main textbooks. There are also differences XIV between tehe number of the words and of the usage of the words used in the writings of the sample groups. 2. It's seen that the mosktly used type of word which is taken part in the textbooks and in the writings of the sample groups is the noun. 3. Turkish words were used more in the textbooks and in the written expressions of the sample- groups than the loanwords. Among the loanwords, the mostly used ones were; Arabic, Persion and French originated words. 4. It's found that the mostly used word taken place in the textbooks and in the writings of the sample groups is a/ an, one. 5. It's seen that the words taken part more in the textbooks are the ones that are used more in the writings of the sample groups. On the other hand, the words used fewer in the textbooks are taken place fewer in the written expressions of the students or are not taken place in the writings.
Keywords: Ders Kitapları; Dil Öğretimi; İlköğretim_Öğrenim ve Öğretim